2020
DOI: 10.21037/atm-20-1040
|View full text |Cite
|
Sign up to set email alerts
|

RNF213 gene polymorphism rs9916351 and rs8074015 significantly associated with moyamoya disease in Chinese population

Abstract: Background: Gene polymorphism especially Ring Finger Protein 213 (RNF213) p.R4810K is one of the main cause of moyamoya disease (MMD) in Asian populations, especially among Japanese people. However, missense mutation may not explain the reduced frequency of MMD in Chinese patients. We performed a hospital based case-control study in a Chinese population to elucidate the possible underlying reasons.Methods: Five gene polymorphism loci, namely, rs35692831, rs9916351, rs9913636, rs8074015 and rs112735431, were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…19 Moreover, although contributing significantly to the genetic burden of MMD, the common variant risk factor RNF213 is represented predominantly in Japanese and other East Asian populations. 16,26,27 Therefore, a significant proportion of MMD remains genetically undefined, especially among the European population. 5,28 The sporadic nature of most MMD cases limits the utility of classic genetic approaches.…”
mentioning
confidence: 99%
“…19 Moreover, although contributing significantly to the genetic burden of MMD, the common variant risk factor RNF213 is represented predominantly in Japanese and other East Asian populations. 16,26,27 Therefore, a significant proportion of MMD remains genetically undefined, especially among the European population. 5,28 The sporadic nature of most MMD cases limits the utility of classic genetic approaches.…”
mentioning
confidence: 99%
“…Both were RNF213 c.14576G > A (p.R4859K, rs112735431). Subsequent studies 7 , 19 23 have also reported the RNF213 polymorphism in MMD, but there is a bias by country 20 . In fact, p.R4810K 22 , which has garnered attention as a susceptibility gene for MMD in East Asians other than p.R4859K, has been reported from Japan 24 , China 22 , 25 , 26 , and Korea 27 .…”
Section: Discussionmentioning
confidence: 99%
“… 169 In a study using a Chinese population, rs9916351 and rs8074015 in RNF213 were demonstrated to be significantly associated with MA. 172 The RNF213 (p.R4810K) variant may predispose individuals of Asian descent living in the United States to MA. 173 Zhang et al 174 identified 27 rare RNF213 missense variants in 255 Chinese MA patients not found in 300 healthy controls.…”
Section: Genetic Biomarkers Of Moyamoya Angiopathymentioning
confidence: 99%